Where does it go? - Miller, Margaret, 1945- (New York : Greenwillow Books, 1992)
Suggests both right and wrong answers for where children should put their socks, doll, crayons, and other possessions.
Keywords: Clothing and dress -- Fiction; Toys -- Fiction